Chemical characterization of two fractions from Sanghuangporus sanghuang and evaluation of antidiabetic activity. (December 2021) - Hou, Ranran; Zhou, Linjiang; Fu, Yan; Wang, Tong; Li, Zhe; Zhou, Liwei; Zhang, Guoli; Tian, Xuemei
Graphical abstract: Highlights: SHP and SHEs were firstly obtained from the fermentation broth of S. sanghuang . SHP and SHEs could significantly promote glucose consumption in vitro . Although SHP possessed hypoglycemic, it inhibited the cytoactive in vitro . SHP have remarkably hypoglycemic effect in typeⅡ diabetes model on mice. Abstract: Sanghuangporus sanghuang polysaccharide (SHP) and ethyl alcohol fractions from the alcohol deposit fluid (SHE) were obtained from the fermentation broth of S. sanghuang . The component analysis by GC–MS showed that 4 organic reagent (petroleum ether, trichloroethane, ethyl acetate and n-butyl alcohol) extractions (SHEs) covered mainly esters, alcohols, phenols, free alkaloids and glycosides. The cytotoxicity and hypoglycemic effect of SHP/SHEs were tested on insulin resistance cell model, the results showed that SHP and SHEs could significantly promote glucose consumption at certain concentrations. Interestingly, SHP not only possessed hypoglycemic, but also inhibited the cytoactive at 2.5–10 mg/mL. Subsequently, the results in type Ⅱ diabetes model on mice revealed that SHP could significantly decrease blood glucose, recover blood lipid levels and repair the damaged tissues at 100–400 mg/Kg·BW. Altogether, our research concluded that SHP possesses antidiabetic activity, suggesting it a prospect application prospect as functional food and medical health product.